Effects of surface coating on the flexural strength of fluoridereleasing restorative materials after water aging for one year - Muhittin Uğurlu (Istanbul University, 2020)
Purpose: To evaluate the effects of surface coating and one-year water storage on the flexural strength of fluoride-releasing restorative materials. Materials and Methods: Forty specimens were prepared from each material; GCP Glass Fill (GCP), Amalgomer CR (AHL), Zirconomer (Shofu), Fuji IX GP Capsule (GC), Beautifil II (Shofu), Estelite Σ Quick (Tokuyama) and reliaFIL LC (AHL). The specimens were randomly divided into two groups; surface coated with G-Coat Plus (GC) and uncoated. Each group was subdivided into two groups stored in distilled water at 37◦C for 24 h and 1 year before testing (n=10). The flexural strength was evaluated using three-point bending test according to the ISO 4049:2009 standard using a universal testing machine. After flexural strength test, a cross-section of the coated specimens was evaluated with scanning electron microscopy (SEM). Results: A significant increase was observed on the flexural strength of Amalgomer CR, Zirconomer and Fuji IX GP after 24 h when G-Coat Plus was applied (p<0.05). This significant increase was observed on the flexural strength of only Amalgomer CR and Zirconomer after 1 year (p<0.05). The highest flexural strength was obtained with Beautifil II, Estelite Σ Quick and reliaFIL LC after 24 h and 1 year (p<0.05). After 1 year, there was decrease on the flexural strength of the other materials except Beautifil II, Estelite Σ Quick and reliaFIL LC. Conclusion: The resin coating improved the flexural strength of some glass ionomer-based materials but the water aging decreased the same physical properties.